Comunidade quilombola São José de Icatu - Baixo Tocantins - Amazônia paraense: condições de vida e lutas, proposta de protocolo de consulta e garantia de direitos quilombolas - BRITO, Maria Delma Portilho (2022)
In this academic work, the São José de Icatu Quilombola Community is initially described under various plans - social, economic, ecological, cultural and political. It is emphasized that in the midst of so much disrespect for the rights of traditional peoples and communities, there is a need to build new tools, as an instrument for the protection and defense of territories, and based on this need, there is a proposal to adopt the construction of a Protocol Consultation, Previa, Free and Informed in the Remaining Community of Quilombo São José de Icatu, aiming that this instrument adds significantly to the struggles and resistance of our quilombola people. The proposal for this construction is based on the research carried out in the activities of the times communities, which took place in the periods from 2016 to 2019, for the Undergraduate course in the Bachelor and Ethnodevelopment Course at the UFPA Campus Altamira / Soure Ethnodiversity Faculty. In this way, the results point to a socioeconomic and environmental diagnosis that reveals problems in aggravating terms, based on observations and reports collected, based on my own experiences while belonging to this quilombo. Elaborating the Consultation Protocol is a challenging project and is part of the action research plan. This will be a pioneer in the region of Baixo Tocantins, in the Paraense Amazon, built autonomously, respecting quilombola demands and specificities, seeking to meet the needs identified in the conversation circles for the elaboration of the Protocol and the previous works of Tempo Comunidade that were densified for elaboration of this Course Conclusion Work.